Innovative treatment for hepatocellular carcinoma (HCC) - Kaneko, Junichi; Kokudo, Takashi; Inagaki, Yoshinori; Hasegawa, Kiyoshi (Translational Gastroenterology and Hepatology; Vol 3 (October 2018): Translational Gastroenterology and Hepatology, 2018)
Indocyanine green (ICG) is not new in the field of liver surgery. Early studies performed in the 1980s and 1990s revealed the value of the ICG clearance test in predicting post-hepatectomy morbidity and mortality. ICG clearance and retention tests are crucial for determining precise liver function before liver surgery and offer several benefits for safe surgery. Whereas ICG is well-known and has long history in medicine, recent progress in infrared light technology over the last decade has highlighted another feature of ICG. For example, ICG fluorescence-guided surgery may change the next generation of liver surgery. In the near future, ICG with near-infrared (NIR) light photodynamic therapy (PDT) is expected to become a new treatment method for hepatocellular carcinoma (HCC). Furthermore, several aspects of the mechanisms of ICG accumulation in HCC cells have been revealed by important basic research studies. New imaging technologies and mechanistic findings keep ICG in the spotlight. In this article, we review three recently described topics of ICG which may contribute to the development of innovative and new treatments method for HCC, fluorescence-guided surgery, mechanism of ICG accumulation in HCC cells, PDT for HCC.